2020
DOI: 10.31235/osf.io/gpt3r
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maintaining contact with blue-green spaces during the COVID-19 pandemic associated with positive mental health

Abstract: There is growing evidence that exposure to the natural world (blue-green spaces) has potential benefits for mental health and well-being. The COVID-19 pandemic and the measures adopted to control it provide a natural experiment to investigate the links between nature exposure and mental health under extreme conditions. Using a survey distributed online and based on 6,080 responses, we tested three hypotheses: (1) people will show different levels of symptoms of depression and anxiety depending on the level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 54 publications
(79 reference statements)
3
20
1
2
Order By: Relevance
“…Access to safe outdoor spaces during periods of physical distancing is critical, particularly considering the rise in rates of self-report loneliness, anxiety, and depression ( Pouso et al, 2020 ). Access to these spaces is important, in part because outdoors is possible to meet people (keeping physical distance), and because parks and streets with green areas are restorative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Access to safe outdoor spaces during periods of physical distancing is critical, particularly considering the rise in rates of self-report loneliness, anxiety, and depression ( Pouso et al, 2020 ). Access to these spaces is important, in part because outdoors is possible to meet people (keeping physical distance), and because parks and streets with green areas are restorative.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of Italian participants, access to views of green areas were associated with a reduction in self-report depression symptoms ( Amerio et al, 2020 ). Similarly, a pre-print study canvassing 77 European countries (61% Spanish sample) found that individuals who maintained contact with natural environments, either through access to private outdoor spaces or blue-green natural viewsheds, reported fewer depression and anxiety symptoms as well as greater self-report positive mood ( Pouso et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increased use of neighbourhood natural environments is likely to contribute to improved human health and well-being (Pouso et al, 2020;Soga et al, 2021), albeit it can, in some cases, have adverse ecological impacts on these environments (e.g. increased pressure on understorey vegetation; Box 1).…”
Section: Pathway 1: Changes In Opportunitymentioning
confidence: 99%
“…For example, in an urban context, increased visits to greenspace caused by the pandemic could promote people's physical and mental health (e.g. Pouso et al, 2020;Soga et al, 2021; Table 1), as well as their emotional affinity towards nature (Grima et al, 2020), which may, in turn, increase their capability and motivation to interact with nature (Figure 2). Likewise, an increase in people's use of nearby (e.g.…”
Section: Feedback Loopsmentioning
confidence: 99%
“…This has already been pointed out in different publications [ 22 , 23 , 24 ]. In an online survey carried out in various European countries within the first COVID-19 wave in 2020, respondents with access to outdoor spaces were less likely to report symptoms of depression and anxiety than individuals with no accessible outdoor spaces [ 25 ]. Based on two surveys in the UK and Scotland, Olsen and Mitchell [ 26 ] also reported mental health benefits from green and open spaces during lockdown.…”
Section: Introductionmentioning
confidence: 99%